Gibberellic acid and naphthalene acetic acid affect fruit retention, yield and quality of keitt mangoes in the coastal Savanna ecological zone of Ghana - Nkansah, G.O.; Ofosu-Anim, J.; Mawuli, A. (American Journal of Plant Physiology, 2012)
Mango production in Ghana is highly reduced by low fruit set. This research was undertaken to apply plant growth regulators to increase fruit set and yield. The present investigation was carried out during two successive years of 2008 and 2009 on Keitt mango trees in order to study the effect of gibberellic acid (GA3) and Naphthalene Acetic Acid (NAA) sprays of different concentration on fruit retention, fruit quality and yield. Trees were sprayed at full bloom stage. The three hormone levels and two location effects were factorially combined and replicated three times in a Randomized Complete Block Design (RCBD). In order to obtain season or year effect, data were analysed as a split-split plot design with season as the main plot, location as sub-plot and cultivar as sub-sub plot. All sprayed chemicals significantly increased fruit retention and tree yield in both seasons. GA3 (25 ppm) and NAA (25 ppm) gave the best results in terms of increasing fruit set, fruit retention, number of fruits per cluster and per plant, fruit weight and yield. No significant differences were observed between the quality of fruits harvested from treated and control trees. 25 ppm of GA3 and 25 ppm NAA can be employed for spraying mango flowers at full bloom to increase mango fruit set, retention and yield of growers. © 2012 Academic Journals Inc.
Keywords: Fruit retention; GA3-NAA; Gibberellic acid; Mangifera indica; Naphthalene acetic acid; Yield